Assessing Soft-Tissue Shrinkage Estimates in Museum Specimens Imaged With Diffusible Iodine-Based Contrast-Enhanced Computed Tomography (diceCT). (19th June 2018) - Hedrick, Brandon P.; Yohe, Laurel; Vander Linden, Abby; Dávalos, Liliana M.; Sears, Karen; Sadier, Alexa; Rossiter, Stephen J.; Davies, Kalina T. J.; Dumont, Elizabeth
Abstract: The increased accessibility of soft-tissue data through diffusible iodine-based contrast-enhanced computed tomography (diceCT) enables comparative biologists to increase the taxonomic breadth of their studies with museum specimens. However, it is still unclear how soft-tissue measurements from preserved specimens reflect values from freshly collected specimens and whether diceCT preparation may affect these measurements. Here, we document and evaluate the accuracy of diceCT in museum specimens based on the soft-tissue reconstructions of brains and eyes of five bats. Based on proxies, both brains and eyes were roughly 60% of the estimated original sizes when first imaged. However, these structures did not further shrink significantly over a 4-week staining interval, and 1 week in 2.5% iodine-based solution yielded sufficient contrast for differentiating among soft-tissues. Compared to six "fresh" bat specimens imaged shortly after field collection (not fixed in ethanol), the museum specimens had significantly lower relative volumes of the eyes and brains. Variation in field preparation techniques and conditions, and long-term storage in ethanol may be the primary causes of shrinkage in museum specimens rather than diceCT staining methodology. Identifying reliable tissue-specific correction factors to adjust for the shrinkage now documented in museum specimens requires future work with larger samples.